Pembangunan Sistem Pengelolaan Manajemen Rumah Indekos pada Indekos Semanggi di Kota Malang - Susiawan Hastomo Ajie; Faizatul Amalia; Agus Wahyu Widodo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
A good boarding house management will fulfill all its necessities. But there is error often occurred in data collecting when applying the boarding house management. The problem comes in Semanggi boarding house, such as takes a long time to find the position of the data. The problems in the data updating is often occurred in incorrect column and row positions, file corruption, delay to update the data, no payment receipts so that the boarders will be charged again when the data is not collected by the boarding house owner. The solution to solve these problems is the owners has to make boarding house management system followed by adding boarding house and boarders features, payment limit notifications, boarding payments, boarding house finance reports, room bookings, boarding house damage reports, printed payment as a proof, data check and also payment status. The development of this boarding house management system is used waterfall model. Unit testing comes to a value 100% valid as the result. The validation test gives 100% value too. The compatibility testing also gives 100% value using ten web browsers.